Mechanisms Applied by Protein Inhibitors to Inhibit Cysteine Proteases - Tušar, Livija (Int J Mol Sci, 2021)
Protein inhibitors of proteases are an important tool of nature to regulate and control proteolysis in living organisms under physiological and pathological conditions. In this review, we analyzed the mechanisms of inhibition of cysteine proteases on the basis of structural information and compiled kinetic data. The gathered structural data indicate that the protein fold is not a major obstacle for the evolution of a protease inhibitor. It appears that nature can convert almost any starting fold into an inhibitor of a protease. In addition, there appears to be no general rule governing the inhibitory mechanism. The structural data make it clear that the “lock and key” mechanism is a historical concept with limited validity. However, the analysis suggests that the shape of the active site cleft of proteases imposes some restraints. When the S1 binding site is shaped as a pocket buried in the structure of protease, inhibitors can apply substrate-like binding mechanisms. In contrast, when the S1 binding site is in part exposed to solvent, the substrate-like inhibition cannot be employed. It appears that all proteases, with the exception of papain-like proteases, belong to the first group of proteases. Finally, we show a number of examples and provide hints on how to engineer protein inhibitors.